Analiza uspešnosti določenih javnih komunikacijskih kampanj na področju varnosti v cestnem prometu v Slovenij - Ašanin Gole, Pedja (Mednarodno inovativno poslovanje, 2019)
Public communication campaigns should alert the addressees to the existence of a social problem and lead to a change of attitudes, knowledge, and behaviour. While some campaigns are greatly echoing within society, are being well accepted, and successfully fulfil their purpose; others are being executed without even being noticed. Every campaign of this kind must be based on theoretical foundations that dictate the way in which they should be strategically planned, managed, and define the type of measures based on which their effectiveness and efficiency can be evaluated. In the article, the authors analyses the effectiveness and efficiency of four 'public communication prevention campaigns' of the Slovenian Public Traffic Safety Agency and, on the basis of the research carried out, determine the extent to which this institution adheres to theoretical principles for the design and implementation of public communication campaigns in its public communication campaigns. The authors used the analysis of secondary documents, structured interview and online survey. The main result of the analysis is that the public communication campaigns in question are poorly planned.
Keywords: campaign evaluation; evalvacija kampanj; Javna agencija RS za varnost prometa; javna komunikacijska kampanja; načrtovanje kampanj; planning campaigns; prevention campaign; preventivna kampanja; public communication campaign; Slovenian Traffic Safety Agency